The Digital Revolution in Small and Medium Enterprises (SMEs): Boosting Operational Efficiency with Information Technology - Rahayu Tri Utami; Fadhila Azzahra; Pamela Larasati; Edy Sambodja (PT. Anagata Sembagi Education, 2024)
The rapid development of information technology has transformed the way many businesses operate, including small and medium-sized enterprises (SMEs). This article explores the impact of implementing information technology on operational efficiency in SMEs. Through case studies and surveys of various SMEs in Indonesia, particularly in Tangerang Raya, data was collected on the use of information technology and changes in operational efficiency. The research results show that process automation is a key factor in improving efficiency, optimizing resource management, reducing operational costs, increasing the speed and accuracy of decision-making, and implementing information technology in SME business processes. This technology enables SMEs to optimize and reduce operational costs, as well as increase customer satisfaction. In addition, this study also found several challenges faced by SMEs in implementing information technology, including limited skilled human resources, high initial costs, and data security issues. Nevertheless, the benefits gained from the use of information technology are much greater than the existing challenges. This article provides recommendations for SME owners and policymakers to support the adoption of information technology, including the provision of training and subsidies for technology investment. In this way, SMEs can become more competitive and contribute more significantly to the national economy.